A Career in Planning. Issue 3 (3rd July 2017) - Christensen, Karen S.
Abstract : In this essay Christensen reviews her 50-year career as a planner, researcher, and teacher. A college summer internship in New York City exposed her to urban problems and initiatives, leading to her thesis and subsequent job at the U.S. Department of Housing and Urban Development, where she worked on interagency and intergovernmental projects. Later she studied at the University of California, Berkeley's, Department of City and Regional Planning, where she became a member of the faculty. In her research and teaching she examined wicked planning problems (Rittel & Webber, 1973), uncertainty in planning, and organizational and intergovernmental decision making, as well as housing. To help students do better at doing good, she taught savvy through a course on planning institutions, and she continues to be engaged with planning theory.